Sustained Product Innovation in Large, Mature Organizations: Overcoming Innovation-to-Organization Problems - Dougherty, Deborah; Hardy, Cynthia (Academy of Management Journal, 1996)
We examined problems with sustained product innovation in 15 firms that averaged 96 years of age, 54,000 employees, and $9.4 billion in annual revenues. Findings reveal that the inability to connect new products with organizational resources, processes, and strategy thwarted innovation in these large, mature organizations and that innovators lacked the power to make these connections. We suggest that these organizations must reconfigure their systems of power to become capable of sustained innovation and offer recommendations for practice.